Soil pest control for maize when applying drip and sprinkler irrigation - F. S. Melnychuk; S. A. Alekseeva; O. V. Hordiienko; L. M. Melnychuk; K. B. Shatkovska (Меліорація і водне господарство, 2020)
In Ukraine, the application of pesticides along with irrigation water (pestigation) is becoming more widespread and popular. The use of insecticides when applying them along with irrigation water on reclamation systems (insecticide method) is a reliable way to reduce the number of dangerous pests. The advantage of this method is the possibility of timely delivery of plant protection products to crops during their critical periods, and rapid application of pesticides regardless of weather conditions.